Use of MRI in the Diagnosis of Fetal Brain Abnormalities in Utero (MERIDIAN): A Multicentre, Prospective Cohort Study. Issue 6 (June 2017) - Griffiths, Paul D.; Bradburn, Michael; Campbell, Michael J.; Cooper, Cindy L.; Graham, Ruth; Jarvis, Deborah; Kilby, Mark D.; Mason, Gerald; Mooney, Cara; Robson, Stephen C.; Wailoo, Allan
Abstract : (Abstracted from Lancet 2017;389:538–546) Ultrasound is routinely used for antenatal screening. One role of antenatal sonography is in the detection of fetal anomalies; among these, fetal brain anomalies occur in almost 3 of every 1000 pregnancies and lead to significant rates of morbidity and mortality.